First record of supernumerary teeth in Glyptodontidae (Mammalia, Xenarthra, Cingulata) - Gonzalez Ruiz, Laureano Raul (2015)
The presence of extra teeth has been reported for nearly all orders of recent mammals but are rarely recorded for fossil mammals. In this contribution we describe the first case of a supernumerary teeth for a Glyptodontidae (Mammalia, Xenarthra) and discuss possible explanations for this phenomenon. The specimen under study corresponds to an almost complete skull of an adult of Boreostemma acostae from the middle Miocene of La Venta (Colombia). Glyptodonts have eight trilobed and triprismatic molariform teeth in each maxilla and dentary (Mf 8/mf 8), but this specimen has nine molariform teeth on the left maxillary series. The sMf is placed between Mf1 and Mf2, with its major axis transversely oriented on the longitudinal axis of the tooth series. Morphologically, this tooth has a very slightly marked lobation, with no labial central lobe, and with two small labial lobes. The supernumerary tooth is within the serial size and form of the dental series. The presence of this supernumerary molariform might be explained by a mutation producing new tooth germen or by a division of an existing tooth germen. Finally, the presence of this supernumerary molariform between the Mf1 and Mf2 appears not to have affected the survival of this specimen, given the adult age of the studied specimen.